High Dose Rate Brachytherapy as a Treatment Option in Endobronchial Tumors. (14th July 2016) - Hosni, Ali; Bezjak, Andrea; Rink, Alexandra; Czarnecka, Kasia; McPartlin, Andrew; Patterson, Susan; Saibishkumar, Elantholiparameswaran
Abstract : Purpose . To report our experience with high dose rate endobronchial brachytherapy (HDR-EBBT) and to assess its efficacy and tolerability with possibility of its use in selected cases with curative intent. Method . Retrospective review of patients with endobronchial tumors treated at our institution in 2007–2013 with HDR-EBBT. Subjective response and treatment related toxicity were extracted from patients' records. Clinical response was evaluated by chest CT +/− bronchoscopy 2-3 months after treatment. Local control (LC) and overall survival (OS) were analyzed. Results . Overall 23 patients were identified. Ten patients were treated with curative intent, in 8 of them HDR-EBBT was combined with external beam radiotherapy. Short term palliation was as follows: dyspnea (13/15), cough (12/14), and hemoptysis (3/3). Seventeen patients were evaluated, of whom 9 (53%) showed complete response. Four patients developed local failure (only 1 of them treated with curative intent) and were salvaged with HDR-EBBT (n = 1 ), chemotherapy (n = 2 ), and laser (n = 1 ). Among patients treated with curative intent, the 2-year LC and OS were 89% and 67%, respectively, and 2 out of 4 deaths were cancer-related. Late toxicity included bronchial stenosis (n = 1 ). Only 1 patient had fatal hemoptysis and postmortem examination indicated local recurrence. Conclusion . HDR-EBBT is promising treatment with tolerable complication if used in properly selected patients.